Education of Covid-19 Preventive and Promotive Efforts Through BUSADICOV - Lusi Lestari; Heni Heryani; Sri Wulan Ratna Dewi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic has an impact on the health of mothers and children. Pregnant women, childbirth, postpartum, and newborns are also vulnerable targets for COVID-19 infection, and this condition is feared to increase maternal and newborn morbidity and mortality. Information about COVID-19 in various mass media and social media often makes people confused. Even though during this global pandemic, some residents still do not have reliable sources of information, especially regarding the health of mothers and children in the face of this pandemic. The purpose of this activity is to increase mothers' knowledge about the Prevention of COVID-19 Transmission to Pregnant Women, Maternity Mothers, Postpartum Mothers, Breastfeeding Mothers, and Newborns. This activity was From March 7, 2021, this activity was carried out until April 7, 2021. This activity was carried out in the form of providing a digital pocketbook on preventing the transmission of COVID-19 to Pregnant Women, Maternity Mothers, Postpartum Mothers, Breastfeeding Mothers, and Newborn Babies (BUSADICOV) at the Posyandu Tangkolo (Jasmine 1) Pawindan Village, Ciamis District. The results of the pretest showed that most of the participants had sufficient knowledge (70%). The posttest results found that most of the participants had good knowledge (66.6%). Community service activities have succeeded in achieving the implementation goal, namely increasing better knowledge after the BUSADICIOV activity has been carried out.